PP.25.16: NOCTURNAL HYPERTENSION IN CHRONIC KIDNEY DISEASE. (June 2015) - Hermida, A.; López, J.E.; Alende, M.J.; Calvo, G.; Pascual, A.; Martínez, V.; Pose, A.; Calvo, C.
Abstract : Objective: The aim of this study was to assess circadian blood pressure pattern and nocturnal hypertension prevalence in those hypertensive subjects with mild-moderate chronic kidney disease. Design and method: A cross-sectional study was conducted among a cohort hypertensive subjects over 18 years old. BP was measured by ambulatory monitoring (ABPM) every 20 min between 07:00 am and 23:00 pm and every 30 min at night, along 48 hours with a Spacelabs 90207 device. The following variables were analysed: age, sex, body mass index (Quetelet), office systolic blood pressure (SBP), office diastolic blood pressure (DBP), 48h-systolic and 48h-dyastolic mean ambulatory blood pressure (48h-SBP and 48h-DBP), 48 h nocturnal systolic and diastolic blood pressure falling. Patients underwent glomerular filtration rate (GFR) as calculated by Modification of Diet in Renal Disease (MDRD), urinary albumin excretion rate (UAER) and microalbuminuria -MAL-. Subjects with advanced renal impairment (CKD stage 5) were excluded. Results: 222 subjects with essential hypertension were included, 160 with preserved renal function and 62 with renal function impairment (CKD-2: 17; CKD-3a: 37; CKD-3b: 6; CKD-4: 2). We didn[Combining Acute Accent]t find any differences on gender, age, weight, body mass index, heart rate or office diastolic BP. Office systolic BP, office pulse pressure and 48h-SBP were higher on those with any stage of CKD. And also regarding nocturnal SBP and nocturnal BP falling, so 74.2% of subjects with CKD had nocturnal hypertension (Vs 57.5%) and 58.1% were "no dipper" (Vs 43.7%). Any subclinical TOD prevalence was higher on those with CKD (85.5% Vs 55.6%), and this difference kept on significant if we only took into account those with mild CKD (stage 2). Conclusions: Even when mild to moderate CKD, office and ambulatory systolic BP is higher if compared to hypertensive subjects with preserved renal function. Moreover, CKD associates to higher nocturnal hypertension prevalence and lower nocturnal systolic BP falling, so a non-dipper circadian BP pattern is more frequent. We suggest both represent potential underlying process of increased cardiovascular risk in that population (even those with mild renal dysfunction).